Modelling of Tritium Breeding For Fusion Blanket Using Geant 4 - Mahamad Zaidi, Nul Alya Aqilah; Mohd Sarif, Ahmad Hassan Sallehudin (Enhanced Knowledge in Sciences and Technology, 2026)
Nuclear fusion is considered a potential future energy source that generates energy cleanly and sustainably. However, a major problem associated with fusion reactors is maintaining a steady fuel supply of tritium, which is done by breeding tritium in a fusion blanket. This research work aims to model and investigate tritium breeding in a conceptual fusion blanket using the Geant4 Monte Carlo simulation framework. It focuses on a multi-layer blanket design consisting of a steel first wall, a lithium ceramic breeder, a beryllium neutron multiplier, and a graphite reflector. A neutron source with an energy of 14.1 MeV is used to copy fusion neutrons. It is seen that tritium is well bred within the lithium ceramic breeder material, and an increase in this breeding is possible with neutrons in beryllium. These findings demonstrate that Geant4 is a reliable tool for modeling tritium breeding, providing valuable insights for the design and optimization of fusion blanket systems in future fusion reactor applications.